Pelatihan Penelitian Tindakan Kelas Untuk Guru-Guru Yayasan - Prihatni, Rida; Sumiati, Ati; Sariwulan, Tuty (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2019)
This activity is an effort to encourage and empower educators to become more professional. This is intended to make efforts to build a solid education, and be able to continually make improvements towards quality. The target audience is high school / vocational teachers of Amal Mulia Education Foundation, Bogor. This training was carried out in several materials, among others, What was the study of class action? Learning models that can be developed in classroom action research, differences in classroom action research with formal research, the initial steps of classroom action research, classroom action research procedures, systematics of classroom action research proposals and examples of classroom action research. From the results during the training, the participants' enthusiasm took place so that it walked live, and the products of PTK titles produced from each participant were then compiled.